2014
DOI: 10.1111/1574-6941.12403
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the immediate and long-term impact on bacterial communities in soil amended with animal and urban organic waste fertilizers using pyrosequencing and screening for horizontal transfer of antibiotic resistance

Abstract: We investigated immediate and long-term effects on bacterial populations of soil amended with cattle manure, sewage sludge or municipal solid waste compost in an ongoing agricultural field trial. Soils were sampled in weeks 0, 3, 9 and 29 after fertilizer application. Pseudomonas isolates were enumerated, and the impact on soil bacterial community structure was investigated using 16S rRNA amplicon pyrosequencing. Bacterial community structure at phylum level remained mostly unaffected. Actinobacteria, Proteoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 66 publications
(89 reference statements)
11
33
1
Order By: Relevance
“…Thus, Poulsen et al (2013a) showed that the effects on microbial diversity of cumulated waste application equivalent of approximately 65 years are very limited. These findings were confirmed by Riber et al (2014), in accelerated treatments having received waste application corresponding to more than 100 years of legal application. Riber et al (2014) also found that fertilizer amendment had only a transient impact on the antibiotic resistance profile of the soil community and that abundance of resistant isolates decreased rapidly with time after fertilizer application, while bacterial community structure at phylum level remained mostly unaffected.…”
Section: The Effect Of Urban Waste Products On Plant and Soil Pte Consupporting
confidence: 52%
See 2 more Smart Citations
“…Thus, Poulsen et al (2013a) showed that the effects on microbial diversity of cumulated waste application equivalent of approximately 65 years are very limited. These findings were confirmed by Riber et al (2014), in accelerated treatments having received waste application corresponding to more than 100 years of legal application. Riber et al (2014) also found that fertilizer amendment had only a transient impact on the antibiotic resistance profile of the soil community and that abundance of resistant isolates decreased rapidly with time after fertilizer application, while bacterial community structure at phylum level remained mostly unaffected.…”
Section: The Effect Of Urban Waste Products On Plant and Soil Pte Consupporting
confidence: 52%
“…These findings were confirmed by Riber et al (2014), in accelerated treatments having received waste application corresponding to more than 100 years of legal application. Riber et al (2014) also found that fertilizer amendment had only a transient impact on the antibiotic resistance profile of the soil community and that abundance of resistant isolates decreased rapidly with time after fertilizer application, while bacterial community structure at phylum level remained mostly unaffected. While changes in bacterial structure below phylum levels cannot be excluded, and risks from accumulation of persistent organic pollutants cannot be ruled out by the studies cited above, they indicate a strong resilience of these soils considering the very high doses applied.…”
Section: The Effect Of Urban Waste Products On Plant and Soil Pte Consupporting
confidence: 52%
See 1 more Smart Citation
“…we performed DESeq2 analyses. The read count tables from the 16S rRNA gene 461 22 profiling and metagenomics sequence analysis, respectively, were aggregated to the 462 family level in R (v. 3 The collection of human and pig fecal specimens as well as sewage was non-invasive, 481 and were performed in accordance with the Declaration of Helsinki, and complied with 482 Table S1A). (C) Ecological richness (Chao 1) and diversity (Shannon index) were determined based on contingency tables from 16S rRNA gene profiling and metagenomic sequencing data at OTU and species levels, respectively (See also Supplemental Table S1B).…”
Section: Differential Abundance Analysis 458mentioning
confidence: 99%
“…Samples were quantified using Quant-iT™ PicoGreen® dsDNA Assay Kit (Invitrogen, Carlsbad, CA) on a Lightcycler 96 (Roche, Mannheim, Germany) and adjusted to equal concentrations. In the second PCR the same conditions were 6 used as in the first round, except the PCR was reduced to 15 cycles and the primers had a unique adaptor/linker/index sequence per sample (3). The PCR products were purified using Agencourt AmPure XP beads (Beckman Coulter Inc, A63881), and concentrations were measured using Quant-iT™ PicoGreen® dsDNA Assay Kit on a Lightcycler 96.…”
Section: Dna Quantitation and Quality Assessmentmentioning
confidence: 99%